Popular economics : unpopular essays - Mahmud, Wahiduddin (Dhaka : University Press, 2002)
Collection of articles and commentaries written by the author for newspapers and occasional lectures delivered in popular forums, with reference to Bangladesh.
Includes bibliographical references and index.
Donated by Akbar Ali Khan
Keywords: Bangladesh -- Economic conditions; Bangladesh -- Economic policy